Self-powered monoelectrodes made from graphene composite films to harvest rain energy. (1st September 2018) - Zhao, Yuanyuan; Pang, Zhibin; Duan, Jialong; Duan, Yanyan; Jiao, Zhengbo; Tang, Qunwei
Abstract: Development of self-powered monoelectrodes for clean energy harvest is a promising solution to meet the growing energy demands for modern electronic device applications. To address this issue, a category of self-powered monoelectrodes are made from cost-effective graphene composite films to harvest rain energy. Periodic current and voltage signals are recorded under rain stimulation to evaluate their rain-to-electricity efficiency. The mechanism behind rain energy harvest arises from charging/discharging cycles of electric π-electron (graphene)|cation (rain) double-layer pseudocapacitances at graphene film/raindrop interface. The maximized current of 2.15 μA/raindrop, voltage of 129.83 μV/raindrop and power of 295.48 pW/raindrop are yielded in the optimized conversion devices. The present work may provide new insights on harvesting waste energies in rain-enriched regions by designing electron-enriched monoelectrodes. Graphical abstract: Image 1 Highlights: Electron-enriched graphene composite films are made by a simple casting technique. Graphene composite films are applied in self-powered monoelectrodes to harvest rain energy. Periodic current, voltage and power signals are recorded under the stimulus of rainwater. Charging/discharging processes of EDL pseudocapacitances contributes to power generation.